2016
DOI: 10.1016/j.appet.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of sweet preference by the actual and anticipated consequences of eating

Abstract: 19Previous research has shown that non-human animals exhibit an inverted-U pattern of sweet 20 preference, with consumption increasing across moderate levels of sweetness and then 21 declining for high levels of sweetness. In rodents, this pattern reflects an avoidance of the 22 postingestive effects of consuming energy-dense sugar solutions (conditioned satiation). 23Here, we examined whether humans also adjust their preferences to compensate for the 24 anticipated energy content / satiating outcomes of consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Although this study found evidence consistent with a SSS effect in that consumption of a sweet drink reduced desire to consume sweet food and drink stimuli more than did consumption of water, in remains possible that at least part of the effect of the sweet drink was to more generally decrease appetite, for example because exposure to sweetness is rewarding and/or satiating (Rogers, 2018;Martin, Ferriday, Rogers & Brunstrom, 2016).…”
Section: Discussionmentioning
confidence: 51%
“…Although this study found evidence consistent with a SSS effect in that consumption of a sweet drink reduced desire to consume sweet food and drink stimuli more than did consumption of water, in remains possible that at least part of the effect of the sweet drink was to more generally decrease appetite, for example because exposure to sweetness is rewarding and/or satiating (Rogers, 2018;Martin, Ferriday, Rogers & Brunstrom, 2016).…”
Section: Discussionmentioning
confidence: 51%
“…It is not clear whether the test beverage (i.e., sucrose-sweetened peach-flavored drink or apricot-flavored nectars) influenced the outcome, as most studies in this scoping review tested sweetness preference with sucrose-sweetened water solutions. Martin et al [47] reported an increased sweetness preference with increased hunger, irrespective of gender. Laeng et al [46] also observed a significantly higher sweetness preference, but only among females in a 'hungry' state compared to their satiated 'fed' counterparts.…”
Section: Dietary/nutritional Factors and Sweetness Preferencementioning
confidence: 97%
“…In 14 studies, the effects of dietary/nutritional factors on sweetness preference were assessed (Table S3-2 of Supplementary File S3). In six of these studies, the effects of a fasted versus fed state on sweetness preference were evaluated [42][43][44][45][46][47]. Only Pangborn [42] reported no significant differences in sweetness preference among participants segregated based on the self-reported level of hunger (consumer study) or based on a fed versus fasted state (laboratory study).…”
Section: Dietary/nutritional Factors and Sweetness Preferencementioning
confidence: 99%